Asymmetrical Parallel Cascaded Microring Resonator (APCMRR) Filter on Silicon-On-Insulator (SOI) for WDM Network - Sahbudin, Saari; Menon, P.S; Ehsan, A.B; Haroon, Hazura (2013)
The integrated development of optical waveguide devices has become the future trend. An optical bandpass filter (OBPF) is typically applied to filter out the required channel from a WDM signal. The present invention provides optical waveguide components of microring structure for wavelength filtering function on silicon-on-insulator (SOI) named APCMRR. The novel design is formed by cascading three microrings in parallel, each comprising different ring radii of 8 μm, 7 μm and 6 μm. A slightly etched silicon waveguide is considered where the height of the silicon waveguide on top of the oxide layer is fixed at 340nm and the fabrication height is 170 nm. The waveguide is approximately single mode, with the TE-mode light propagating around 1550nm for 400nm waveguide width and the coupling distance between all waveguides is 100nm. Using commercially available numerical software of Fullwave by Rsoft Inc., the investigation show that the calculated free spectral range (FSR) value is 11nm with low insertion loss of 0.21dB. A flat top, steep roll-off and a high out of band rejection 45dB and minimum sidelobes was achieved. In addition, the invention has proven to work well as the OBPF for 200 GHz channel spacing, 8x10 Gbps WDM networks applications.